Magnetic Resonance Findings in Adolescent Vaginal Rhabdomyosarcoma: A Rare Case Report - Trifonia Pingkan; Fitri Juniarta; Hartono Tjahjadi; Meliyana Lai (Indonesian Journal of Cancer, 2022)
Introduction: Rhabdomyosarcoma (RMS) is a rare soft tissue tumor, mainly affecting children, adolescents, and adults younger than 15 years, representing 3% to 4% of all childhood malignancies. Genitourinary is the second-most-common location of RMS with around 25% of cases. We describe a rare case of vaginal rhabdomyosarcoma in adolescents with huge polypoid tumors. Case Presentation: A 15-year-old female presented with vaginal bleeding for seven months. Her medical story was unremarkable. The clinical examination showed a polypoid mass prolapsed from the vagina, and the laboratory result was anemia. The pelvic magnetic resonance imaging (MRI) showed a heterogenous bulky solid tumor in the vagina. The histopathological finding revealed a sarcoma, and the immunohistochemical staining result was rhabdomyosarcoma not otherwise specified (NOS). Conclusions: Vaginal RMS is a rare malignant tumor of mesenchymal origin with skeletal muscle differentiation. Vaginal RMS is the most common site of genitourinary RMS and presents as a rapidly growing and aggressive local mass. Imaging plays an important role in the initial diagnosis of vaginal RMS, regarding the presentation of the bulky protruding tumor on the vaginal region